2007
DOI: 10.1038/sj.onc.1210521
|View full text |Cite
|
Sign up to set email alerts
|

Expression profiling of Ral-depleted bladder cancer cells identifies RREB-1 as a novel transcriptional Ral effector

Abstract: Although the monomeric GTPases RalA and RalB have been shown to regulate a variety of transcription factors, little is known regarding the differences or similarities in transcriptional programs regulated by RalA compared to RalB. Further, the association of these transcriptional pathways to human carcinogenesis and progression remains unclear. Here, we studied the role of RalA and/ or RalB in transcriptional regulation by combining short interfering RNA depletion of Ral with gene expression profiling via micr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
22
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 31 publications
0
22
0
Order By: Relevance
“…RREB1 is a transcription factor that has been reported to be either an activator, [22][23][24] or a repressor 25-28 of gene expression, the action of which is dependent upon the gene and cell type. 29 Our results reveal that REEB-1 is a positive regulator of ZIP3 gene expression. Consequently, the existence of downregulated RREB1 in PanIN and early malignancy must be accompanied by preceding upstream events that promote the downregulation of RREB1.…”
Section: Discussionmentioning
confidence: 87%
“…RREB1 is a transcription factor that has been reported to be either an activator, [22][23][24] or a repressor 25-28 of gene expression, the action of which is dependent upon the gene and cell type. 29 Our results reveal that REEB-1 is a positive regulator of ZIP3 gene expression. Consequently, the existence of downregulated RREB1 in PanIN and early malignancy must be accompanied by preceding upstream events that promote the downregulation of RREB1.…”
Section: Discussionmentioning
confidence: 87%
“…Despite its implication in Ras, Ral, p16, p53, and androgen receptor 10,11,14,19,20 signaling pathways, sparse data exist regarding the nature, expression, or function of RREB1 mRNA and protein in cancer cells. This is the first study to address this gap by describing RREB1 expression in human cancers, as well as the first to examine isoform expression in human tissues and cell lines.…”
Section: Discussionmentioning
confidence: 99%
“…8,9 Notably, the RREB1 (Rasresponsive element binding protein 1) transcription factor was identified as a putative Ral-regulated gene through batch analysis of promoter sequences in Ral target genes. 10 Experiments confirmed that Ral manipulation affects RREB1 reporter activity in bladder cancer cells. 10 The significance of RREB1 continues to be elucidated as studies have found it to function in either the induction or repression of gene expression.…”
mentioning
confidence: 80%
See 1 more Smart Citation
“…Neither study implicated RALB in the generation of primary tumours; however, the Counter group found that chronic RALB depletion severely impaired or eliminated the capacity of several pancreatic cancer lines to generate lymph-node metastases following tail vein injection 10 . Interestingly, Ral-dependent gene-expression patterns that might contribute to metastatic behaviour have recently been uncovered by genomic expression profiling 25,26 . Although these studies clearly convict Ral proteins as key offenders in the maintenance of tumorigenicity, further work is needed to determine whether the biological consequences observed reflect distinct contributions of Ral signalling to tumorigenicity in diverse cell types, and/ or distinct sensitivities to the tissue microenvironment, and/or differences in phenotypic penetrance as a consequence of residual RALA or RALB protein expression.…”
Section: Box 1 | the G-protein Cyclementioning
confidence: 99%